# Extensions 1→N→G→Q→1 with N=C2×2- 1+4 and Q=C2

Direct product G=N×Q with N=C2×2- 1+4 and Q=C2
dρLabelID
C22×2- 1+464C2^2xES-(2,2)128,2324

Semidirect products G=N:Q with N=C2×2- 1+4 and Q=C2
extensionφ:Q→Out NdρLabelID
(C2×2- 1+4)⋊1C2 = (C2×Q8)⋊16D4φ: C2/C1C2 ⊆ Out C2×2- 1+432(C2xES-(2,2)):1C2128,1742
(C2×2- 1+4)⋊2C2 = (C2×Q8)⋊17D4φ: C2/C1C2 ⊆ Out C2×2- 1+464(C2xES-(2,2)):2C2128,1745
(C2×2- 1+4)⋊3C2 = C2×D4.8D4φ: C2/C1C2 ⊆ Out C2×2- 1+432(C2xES-(2,2)):3C2128,1748
(C2×2- 1+4)⋊4C2 = M4(2).C23φ: C2/C1C2 ⊆ Out C2×2- 1+4328-(C2xES-(2,2)):4C2128,1752
(C2×2- 1+4)⋊5C2 = C22.75C25φ: C2/C1C2 ⊆ Out C2×2- 1+432(C2xES-(2,2)):5C2128,2218
(C2×2- 1+4)⋊6C2 = C22.76C25φ: C2/C1C2 ⊆ Out C2×2- 1+432(C2xES-(2,2)):6C2128,2219
(C2×2- 1+4)⋊7C2 = C22.78C25φ: C2/C1C2 ⊆ Out C2×2- 1+432(C2xES-(2,2)):7C2128,2221
(C2×2- 1+4)⋊8C2 = C4⋊2- 1+4φ: C2/C1C2 ⊆ Out C2×2- 1+464(C2xES-(2,2)):8C2128,2229
(C2×2- 1+4)⋊9C2 = C22.88C25φ: C2/C1C2 ⊆ Out C2×2- 1+464(C2xES-(2,2)):9C2128,2231
(C2×2- 1+4)⋊10C2 = C22.89C25φ: C2/C1C2 ⊆ Out C2×2- 1+432(C2xES-(2,2)):10C2128,2232
(C2×2- 1+4)⋊11C2 = C2×D4○SD16φ: C2/C1C2 ⊆ Out C2×2- 1+432(C2xES-(2,2)):11C2128,2314
(C2×2- 1+4)⋊12C2 = C2×Q8○D8φ: C2/C1C2 ⊆ Out C2×2- 1+464(C2xES-(2,2)):12C2128,2315
(C2×2- 1+4)⋊13C2 = C4.C25φ: C2/C1C2 ⊆ Out C2×2- 1+4328-(C2xES-(2,2)):13C2128,2318
(C2×2- 1+4)⋊14C2 = 2- 1+6φ: C2/C1C2 ⊆ Out C2×2- 1+4328-(C2xES-(2,2)):14C2128,2327
(C2×2- 1+4)⋊15C2 = C2×C2.C25φ: trivial image32(C2xES-(2,2)):15C2128,2325

Non-split extensions G=N.Q with N=C2×2- 1+4 and Q=C2
extensionφ:Q→Out NdρLabelID
(C2×2- 1+4).1C2 = 2- 1+42C4φ: C2/C1C2 ⊆ Out C2×2- 1+432(C2xES-(2,2)).1C2128,525
(C2×2- 1+4).2C2 = (C22×Q8)⋊C4φ: C2/C1C2 ⊆ Out C2×2- 1+4328-(C2xES-(2,2)).2C2128,528
(C2×2- 1+4).3C2 = C23.4C24φ: C2/C1C2 ⊆ Out C2×2- 1+4328-(C2xES-(2,2)).3C2128,1616
(C2×2- 1+4).4C2 = M4(2).25C23φ: C2/C1C2 ⊆ Out C2×2- 1+4328-(C2xES-(2,2)).4C2128,1621
(C2×2- 1+4).5C2 = 2- 1+44C4φ: C2/C1C2 ⊆ Out C2×2- 1+464(C2xES-(2,2)).5C2128,1630
(C2×2- 1+4).6C2 = Q8.(C2×D4)φ: C2/C1C2 ⊆ Out C2×2- 1+464(C2xES-(2,2)).6C2128,1743
(C2×2- 1+4).7C2 = C2×D4.10D4φ: C2/C1C2 ⊆ Out C2×2- 1+432(C2xES-(2,2)).7C2128,1749
(C2×2- 1+4).8C2 = C4×2- 1+4φ: trivial image64(C2xES-(2,2)).8C2128,2162

׿
×
𝔽